CDC7/DBF4 functions in the translesion synthesis branch of the RAD6 epistasis group in Saccharomyces cerevisiae. - Pessoa-Brandão, Luis (2004)
CDC7 and DBF4 encode the essential Cdc7-Dbf4 protein kinase required for DNA replication in eukaryotes from yeast to human. Cdc7-Dbf4 is also required for DNA damage-induced mutagenesis, one of several postreplicational DNA damage tolerance mechanisms mediated by the RAD6 epistasis group. Several genes have been determined to function in separate branches within this group, including RAD5, REV3/REV7 (Pol zeta), RAD30 (Pol eta), and POL30 (PCNA). An extensive genetic analysis of the interactions between CDC7 and REV3, RAD30, RAD5, or POL30 in response to DNA damage was done to determine its role in the RAD6 pathway. CDC7, RAD5, POL30, and RAD30 were found to constitute four separate branches of the RAD6 epistasis group in response to UV and MMS exposure. CDC7 is also shown to function separately from REV3 in response to MMS. However, they belong in the same pathway in response to UV. We propose that the Cdc7-Dbf4 kinase associates with components of the translesion synthesis pathway and that this interaction is dependent upon the type of DNA damage. Finally, activation of the DNA damage checkpoint and the resulting cell cycle delay is intact in cdc7Delta mcm5-bob1 cells, suggesting a direct role for CDC7 in DNA repair/damage tolerance.